Implications of Project-Citizent Based Civic Education Learning: The Key to Obtaining Civic Competence? - Rafzan, Rafzan (Abdimas Galuh, 2024)
The ability of citizens in civic education must have four components of ability, namely civic knowledge, civic skill, civic value and civic action. The four competencies of citizens are the most dominant things to be applied. This ability facilitates students in acting and thinking critically to solve problems in various social situations. That ability requires efficient expertise. In line with the overall competence, competence can also determine problem solving in learning. The implementation of this learning is based on obtaining the four competencies. This can determine the attitude of awareness and critical thinking of citizens in optimizing their abilities. The application of project-citizent-based  learning to lead how a student as a citizen can obtain civic competence through a problem-solving process with the project citizent learning model. The four competencies are civic knowledge, civic skill, civic value and civic action, which are obtained when they explain the problem with their assumptions and reflect on the urgency of the problem that has been studied, civic skill is obtained when they optimize their role in solving problems by comparing various opinions from experts, civic value obtained when solving problems accompanied by solutions as a form of value or result of their studies, and civic actions are obtained when they act according to expectations and reality. Thus, it can be concluded that through learning the citizen project model,  the problem-solving process can move citizens to grow and develop in a society that prioritizes awareness as citizens, thinking skills, values and positive attitudes of citizens (civic competence). This is due to the process and way students investigate the urgency of the problem and identify the problem, formulate the problem and determine the solution through the project citizen model.